Individual and Contextual Factors Related to Secondary Special Education Teachers' Reading Instructional Practices. (February 2018) - Leko, Melinda M.; Chiu, Ming Ming; Roberts, Carly A.
This article reports findings from an initial investigation of the impact multiple individual and contextual factors have on secondary special educators' reading instructional practices. Data from 577 special educators from 221 school districts in a large Midwestern state were collected via an online and paper survey and analyzed using multivariate, multilevel, logit analyses. Results suggest four clusters of factors—teacher preparation, instructional freedom, student characteristics, and service delivery model—were significantly related to teachers' practice in explicit word study, fluency, vocabulary, and comprehension instruction. Implications for future research and practice in special education teacher quality in reading for adolescents with disabilities are discussed.